UMPSA prepares to conquer Mount Kinabalu - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUALA LUMPUR, 14 September 2023 - The Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Expedition Team, consisting of eight climbers, including students, alumni, and staff, is gearing up to conquer Mount Kinabalu in the Mount Kinabalu Summit Expedition Mission.